Inclusive Teaching Award - Charalambous, Marina (My University, 2026)
Faculty member Dr Marina Charalambous (Special Teaching Staff) was honoured with the Inclusive Teaching Award, as part of the Íntabou campaign “I Learn in My Own Way” organised by the EUt+ Coordinating Centre. This recognition comes from the student community and acknowledges the inclusive teaching practices implemented in their courses, which promote an open, supportive, and equitable learning environment for all.
Keywords: Education